Social computing through business-based: Tamu Gadang portal - Baharum A.; Wahab S.H.A.; Ismail R.; Mat Noor N.A.; Fabeil N.F.; Ab Fatah N.S. (Association for Computing Machinery, 2023)
Artificial intelligence; Industry; Business domain; Social; Social computing; Social context; Social convention; Systems development; Virtual reality